2006
DOI: 10.1529/biophysj.105.071209
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Dynamics of Breakage of Fluorescent Microtubules

Abstract: The breakage of fluorescence-labeled microtubules under irradiation of excitation light is found in our experiments. Its mechanism is studied. The results indicate that free radicals are the main reason for the photosensitive breakage. Furthermore, the mechanical properties of the microtubules are probed with a dual-optical tweezers system. It is found that the fluorescence-labeled microtubules are much easier to extend compared with those without fluorescence. Such microtubules can be extended by 30%, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
19
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 22 publications
6
19
0
1
Order By: Relevance
“…In addition, Guo et al showed that irradiation of rhodamine-tags triggers depolymerization of MT upon laser exposure [26], thus indicating that visible light could be used to affect the formation of MT. With the current investigation we have studied whether i.)…”
mentioning
confidence: 99%
“…In addition, Guo et al showed that irradiation of rhodamine-tags triggers depolymerization of MT upon laser exposure [26], thus indicating that visible light could be used to affect the formation of MT. With the current investigation we have studied whether i.)…”
mentioning
confidence: 99%
“…However, Cy3 is brighter and more photostable than rhodamine derivatives, allowing a lower labeled/unlabeled tubulin ratio to be used while still easily visualizing MTs. Finally, whereas rhodamine MTs suffer light-induced structural damage resulting from the formation of reactive oxygen species (ROS) [61, 62], we have found Cy3 MTs to be less affected (we also use an oxygen scavenging system to eliminate ROS in either case). …”
mentioning
confidence: 99%
“…As previously reported, fluorescence microscopy can induce photochemical reactions that produce ROS in the presence of oxygen. ROS produced during sample obeservation using fluorescence microscopy can damage biomolecular motors, 32,33 resulting in the loss of activity. Using the ICS, we removed oxygen from the system and demonstrated that the AcSO of MTs could be performed in an oxygen-free inert atmosphere.…”
Section: Resultsmentioning
confidence: 99%